2007
DOI: 10.1016/j.mce.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol-A alters gene expression and functional parameters in molluscan hepatopancreas

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.A c c e p t e d M a n u s c r i p t A c c e p t e d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 62 publications
(111 reference statements)
3
32
0
Order By: Relevance
“…Thus the findings of Canesi et al (2007a) may have significant implications for mussel health. Canesi et al (2007b) also reported altered patterns of gene expression and activity of enzymes involved in the redox balance following an injection of BPA into the posterior adductor muscle (at nominal doses of 3, 15 and 60 ng BPA g 21 dry wt.). In the digestive gland, an increased expression of the Mytilus ER (MeER2) was observed at the lowest test concentration 24 h after injection, whereas results for the higher test concentrations were not significant.…”
mentioning
confidence: 94%
“…Thus the findings of Canesi et al (2007a) may have significant implications for mussel health. Canesi et al (2007b) also reported altered patterns of gene expression and activity of enzymes involved in the redox balance following an injection of BPA into the posterior adductor muscle (at nominal doses of 3, 15 and 60 ng BPA g 21 dry wt.). In the digestive gland, an increased expression of the Mytilus ER (MeER2) was observed at the lowest test concentration 24 h after injection, whereas results for the higher test concentrations were not significant.…”
mentioning
confidence: 94%
“…The major injury known for BPA is the endocrine disruption [4,17]. The evaluation of the ALP detected this typical effect − the increase of the level of these vitellogenin-like proteins in the gonads of male specimens, despite in the hemolymph their level was not changed by exposure.…”
Section: таблиця 3 біомаркери токсичності у травній залозі (Dg) гемmentioning
confidence: 95%
“…The evaluation of the ALP detected this typical effect − the increase of the level of these vitellogenin-like proteins in the gonads of male specimens, despite in the hemolymph their level was not changed by exposure. The endocrine disruptive effects of BPA were shown earlier in marine mussels affecting significantly their reproduction [1,4].…”
Section: таблиця 3 біомаркери токсичності у травній залозі (Dg) гемmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, for prosobranch snails, bisphenol A can induce ''superfemale'' development characterized by formation of additional female organs, enlargement of accessory glands, malformations of oviducts, massive stimulation of oocytes and spawning (Oehlmann et al 2000;Jobling et al 2003), and increases in the number of embryos sheltered in the brood pouch (Duft et al 2003). Bivalves may also be affected by bisphenol A: injection of bisphenol A into Mytilus alters antioxidant levels, decreases lysosomal membrane stability and increases neutral lipid accumulation in the hepatopancreas (Canesi et al 2007), and modulates kinase-mediated signaling pathways (Canesi et al 2004). Zebra mussels exposed to effluent from a municipal sewage treatment works (containing bisphenol A) have increased vitellin-like proteins and alterations in morphology of male genitalia (Quinn et al 2004).…”
Section: Introductionmentioning
confidence: 99%